A Cruise Line Dynamic Overbooking Model with Multiple Cabin Types from the View of Real Options. (May 2014) - Li, Bingzhou
The fundamental booking decision for a cruise line involves how many reservations to accept to avoid two outcomes—either sailing with empty cabins or denying some customers' bookings. Cruise lines accept reservations that overbook a cruise because they anticipate a number of cancellations and no-shows. The question is how many overbooked reservations to accept such that no one is denied boarding. This article applies a real options approach to formulate a risk decision model for cruise line dynamic overbooking. The analysis includes multiple cabin types and allows upgrading to reduce and avoid the two reservation risks. This article illustrates the way to find the best overbooking level vector. The analysis models a series of real options contained in the joint overbooking decision. Furthermore, the dynamic joint overbooking decision is analyzed and discussed from the view of various types of real options. Finally, numerical examples are used to demonstrate how to solve the joint overbooking problem with two given decision schemes using the real options analysis (ROA) in real-time.